Rapidly grown KDP crystals - Salo, V.I. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2000)
Results of the study of optical characteristics, real structure and laser damage threshold of KDP crystals rapidly grown in the direction of a prespecified angle of synchronism (θ = 59°) are described in the present paper. A comparative analysis of KDP characteristics for crystals grown by conventional method at a rate of 1 mm/day and by the method of oriented growth at a rate of 10 mm/day is presented. It is shown that elaborated method allows to obtain blanks of nonlinear elements already at the stage of growth. The grown crystals have the bulk laser damage threshold on the level of ~5⋅10¹⁰ cm² and high structure quality; thus it allows to apply them as multipliers of laser radiation frequency.